Study of sleep disturbances in frontline healthcare workers during COVID-19 epidemic - Kumari, Deepika; Beena (International Journal of Research in Medical Sciences, 2023)
Background: Aim of this study was to study sleep disturbances in frontline healthcare workers during COVID-19 epidemic. Methods: This is a case control study was conducted in the Department of Physiology at Pt. B. D. Sharma PGIMS, Rohtak. The study included hundred volunteer subjects of age group 25-35years and were divided into two groups (healthcare workers and and professionals from non-medical background). Results: Subjective sleep quality was significantly altered in FHCW with P value of 0.001. Sleep latency was increased in study group with 50% of study group having score of 3 on Pittsburg sleep quality index. The duration of sleep was reduced in study group with increased sleep disturbances. Forty percent of FHCW reported use of medications for sleep. Almost 100% of FHCW reported Day time dysfunction. Conclusions: COVID-19 resulted in significant sleep deprivation, increased latency, poor sleep quality and increased use of medication in FHCW. The FHCW suffered from poor quality of sleep during the COVID pandemic. FHCW were affected by several stress factors including heavy workload, high night shift frequency and constant use of PPE kit. All these stress factors affected their quality of sleep.